Single‐port and multi‐port frequency‐dependent network equivalents with numerically stable branches. Issue 3 (20th November 2017) - Moghimi Haji, Moosa; Xu, Wilsun; Geng, Guangchao
Abstract : This study proposes new methods for finding frequency‐dependent network equivalents of power systems. Since stability of the time‐domain solution is a major concern, additional constraints are added to ensure the stability in both single‐port and multi‐port network equivalents. For single‐port problem, an equivalent circuit consisting of only passive elements is estimated to ensure passivity and, consequently, stability of the time‐domain solution. For multi‐port case, additional stable branches are added to fit the frequency response data with high accuracy while maintaining stability of the equivalent. Several case studies are considered to evaluate the performance of the proposed approaches. The simulation results prove the efficacy of the proposed methods for finding stable equivalent circuits with high accuracy.